Beyond Curvature: Prevalence and Characteristics of Penile Volume-Loss Deformities in Men With Peyronie's Disease. Issue 4 (17th October 2018) - Margolin, Ezra J.; Pagano, Matthew J.; Aisen, Carrie M.; Onyeji, Ifeanyi C.; Stahl, Peter J.
Abstract: Introduction: Non-curvature penile deformities associated with loss of erect penile volume are often overlooked and have not been thoroughly investigated. Aim: To describe the prevalence and functional impact of penile volume-loss deformities in our cohort of men with Peyronie's disease (PD). Methods: We retrospectively examined medical records of patients with PD consecutively evaluated by a specialized urologist from December 2012 to June 2016. We excluded patients with prior surgical correction of PD, prior penile prosthesis, and inadequate erection during office examination. All patients underwent deformity assessment of the erect penis after intracavernosal injection. The assessment included measurement of penile curvature; evaluation for hourglass deformities, indentations, and distal tapering; and application of axial force to assess for penile buckling. Prior to the deformity assessment, each patient completed the Male Sexual Health Questionnaire and was asked if he experienced psychological distress and functional impairment related to his penile deformity. Main Outcome Measure: The primary clinical parameters that we evaluated were presence or absence of axial instability, functional impairment, psychological distress, penile pain, erectile dysfunction, ejaculatory dysfunction, sexual dissatisfaction, decreased sexual activity, and decreased sexual desire. Results: 128 patients met criteria for inclusion. 83 patients (65%) had volume-loss deformities. Unilateral indentations, hourglass deformities, and distal tapering were present in 50 (39%), 30 (23%), and 16 (13%) patients, respectively. Penile curvature <10° degrees was present in 115 patients (90%). After controlling for angle of curvature, patients with volume-loss deformities had significantly higher rates of axial instability (odds ratio [OR] = 3.5, P = .01) and psychological distress (OR = 2.6, P = .03), as well as decreased sexual activity (OR = 2.7, P = .02), than patients with non–volume-loss deformities. Conclusion: Volume-loss penile deformities are highly prevalent in men with PD. These deformities are associated with penile axial instability and psychological distress, which may contribute to decreased frequency of sexual activity.